IMPROVING SCIENCE LITERACY COMPETENCE OF GRADE VII STUDENTS THROUGH THE IMPLEMENTATION OF PROJECT-BASED LEARNING - Aisyah Rohmatin, Siti; Andari, Tri; Baity, Nur (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2023)
The aim of this research is to find out the increase in the ability of students in scientific literacy after the Project Based Learning model is applied in their learning. This type of research is classroom action research. The research subjects consisted of 32 students in class VII E of SMPN 1 Bojonegoro for the 2022/2023 academic year. The data collection techniques used tests and observations. AKM-based formative tests and observation sheets are used for the data collection instruments. Processing the value of students' abilities in scientific literacy is calculated using the calculation of the percentage between the correct score and the maximum total score. The test results obtained are grouped into 5 categories; Very Good, Good, Adequate, Poor, and Very Poor. The results of the study show that the scientific literacy skills of students' competence on indicators of explaining a phenomenon scientifically, conducting evaluations and compiling scientific investigations, and interpreting scientific evidence have increased with an average score in pre-cycle learning of 67.58 which is in the adequate caegory and in cycle II follow-up increased to 83.58 which was in the Good category. The conclusion from this study is that the implementation of Project Based Learning is proven to be able to improve the scientific literacy skills of students in class VII E of SMP Negeri 1 Bojonegoro for the 2022/2023 academic year. Keywords: Science Learning, Project Based Learning, Competency Science Literacy Ability